Tracing the Development of Santri Proficiency in Reading The Book of Fathul Qarib With A Mathematical Model - Ulfiyati, Nur Shofa; Yahadiana, Fahdina; Hidayat, Rahmat (Journal of Multidisciplinary Sustainability Asean, 2024)
Background. Santri are the main object in the learning process of the yellow book. The success of the yellow book education cannot be separated from the aspect of the ability of the students to read and understand the book. One of the yellow books that are widely studied in all pesantren is the book of Fathul Qarib. Purpuse. This study seeks to trace developments in learning to read and understand the yellow book with a mathematical model approach. Mathematical models are a branch of mathematics that attempts to photograph and translate a phonomene in life into a representation of mathematical equations that describe this phenomenon. Method. This research is a combination of fieldwork and literature study. This research was conducted at Pondok Pesantren Al Munawwir Krapyak Komplek Q in Krapyak Hamlet, Panggung Harjo Village, Sewon District, Bantul Regency, Yogyakarta Special Region Province. The object of this research is the students of Al Munawwir Krapyak Islamic Boarding School Komplek Q Awwal Class, Tsani and Tsalis who are studying the book of Fathul Qarib. Results. This research results that the mathematical model of the development of the students' ability to read the Fathul Qarib book at the Al-Munawwir Q Krapyak Islamic Boarding School, Yogyakarta is: K (t) = 55e^((0.1447) t) and based on parameter estimates from year 0 of 55, Year 1 is 63.563, year 2 is 73.459, and year 3 is 84.897. Conclusion. This means that the development of the students' ability in reading the book Fathul Qarib will continue to increase until the students can really master and understand the book.